Reining in plasticulture from land to sea: Pacific Northwest (USA) perspectives on agriculture and aquaculture - Brander, Susanne M.; Langellotto, Gail A.; Mistry, Minal T.; Singleton, Sebastian L.; Hainey, MacKenna A.; Kashiwabara, Lauren M.; Arthur, Kelsey; Granek, Elise F.; Baird, Kervelle; Palazuelos, Ricardo; Campos, Nayeli; Trim, Heather; et al. (Frontiers in Sustainable Food Systems, 2025)
Plastic use in food production—known as plasticulture—has transformed agriculture and aquaculture globally. Plasticulture gained momentum in the mid-20th century with the development of novel plastic materials, and by 2009, U.S. farmers used over 200 million pounds of plastic films annually. Though plastics have increased yields and efficiency, they now pose environmental hazards through the release of microplastics (MPs) and chemicals. Despite extensive documentation of MPs in the environment, their role in U.S. food production and impacts on crop, livestock, and aquaculture health remain underexplored. In regions like the Pacific Northwest (PNW), with robust agricultural and aquaculture sectors, plastics from films, mulches, cages, and ropes are significant sources of MPs. Soil amendments like biosolids and compost also contribute MPs from household waste. Agricultural plastics accounted for 3–5% (10–18 million tons) of global plastic production in 2018 and are projected to increase due to growing food demand. Aquaculture uses an estimated 2.1 million tons of plastics annually, but detailed data on MP generation is lacking. Despite known environmental concerns, a sustainable circular model for plastics in food systems is still absent, but necessary. While biodegradable products for use in farming and aquaculture have been introduced, high costs, regulations, and practical limitations hinder widespread adoption. Until recently, the American Society for Plasticulture (ASP) primarily focused on new plastic innovations rather than sustainability. Now, growing awareness of plastic pollution and health risks has led to increased scrutiny. In the PNW—home to key specialty crops and 6% of U.S. aquaculture operations—there is an urgent need for coordinated efforts to reduce plastic contamination. Shifting toward sustainable practices is challenging but critical to protect ecosystems, food safety, and public health, and possible through regional and state-level regulations on composting, wastewater and biosolids mitigation, and movement to more sustainable replacements where feasible. As our knowledge of micro and nanoplastic impacts on the food supply at sea and on land increases, approaches to reduce the use of plastics overall and to limit leaching and fragmentation into crops, seafood, and meat is essential to protecting human and environmental health. Regulatory efforts at the regional, national and global levels are needed to enhance food safety.